RICARDO PIGLIA EN LOS 60: LOS INICIOS DE UNA POÉTICA FUTURA (AÑOS DE FORMACIÓN). - Fernández Cobo, Raquel (Revista Chilena de Literatura, 2018)
This paper studies the importance of Ricardo Piglia's work, especially in Los diarios de Emilio Renzi (2015 and 2016), his intellectual activity both in literary journals and in the publishing company Tiempo contemporáneo in the 1960s, a time of great revolutionary fervour, marked by the union of aesthetics and politics advocated by a Nueva Izquierda. The article focuses on the analysis of the magazine Literatura y sociedad (1965) and his work as editor of Tiempo Contemporáneo (1966-1968), while developing a cross reading with his journals.